Czech countryside - strategies of regional development - Cudlínová, Eva; Rolínek, Ladislav; Faltová Leitmanová, Ivana; Klufová, Renata; Jílek, Milan (Wydawnictwo Uczelniane Zachodniopomorskiego Uniwersytetu Technologicznego w Szczecinie, 2013)
Our paper tries to answer the question of the role of internal factors such as characteristics of local governance within the process of rural development. We focused on development of villages within rural areas of the Czech Republic (CR). We used increasing number of population during our analysed period as a rough indicator of village prosperity. This indicator reflects a different level of combination of two factors - rate of population growth and rate of migration in our time period. This philosophy is based on the idea that living village means successful village also in terms of economic prosperity. This paper is focused on deeper analysis of mayors´ interviews. Mayors as main representatives of local governance are the proper persons in terms of strategic development of village. Our results revealed that, the strategies of mayors and local community activity are the key factors for successful development and village prosperity.
Český venkov - strategie regionálního rozvoje
Keywords: Rural development; strategy of development; factors of development; rural policy; mayors visions; Rozvoj venkova; strategie rozvoje; faktory rozvoje venkova; rurální politika; rozvojové vize starostů